2021
DOI: 10.1016/j.evolhumbehav.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Facial metrics generated from manually and automatically placed image landmarks are highly correlated

Abstract: Research on social judgments of faces often investigates relationships between measures of face shape taken from images (facial metrics), and either perceptual ratings of the faces on various traits (e.g., attractiveness) or characteristics of the photographed individual (e.g., their health). A barrier to carrying out this research using large numbers of face images is the time it takes to manually position the landmarks from which these facial metrics are derived. Although research in face recognition has led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…(2014) using a statistically well-powered sample of 520 UFC fighters using computer-automated fWHR measurements. Recent research suggests an advantage, when using large datasets, in employing anthropometric measurements generated automatically using programmed algorithms (Jones et al, 2021). Study 1 also extended Dixson et al, 2018;Lane & Briffa, 2020).…”
Section: The Present Workmentioning
confidence: 84%
See 2 more Smart Citations
“…(2014) using a statistically well-powered sample of 520 UFC fighters using computer-automated fWHR measurements. Recent research suggests an advantage, when using large datasets, in employing anthropometric measurements generated automatically using programmed algorithms (Jones et al, 2021). Study 1 also extended Dixson et al, 2018;Lane & Briffa, 2020).…”
Section: The Present Workmentioning
confidence: 84%
“…In Study 1, we aimed to replicate the significant associations of Zilioli et al (2014) using a statistically well‐powered sample of 520 UFC fighters using computer‐automated fWHR measurements. Recent research suggests an advantage, when using large datasets, in employing anthropometric measurements generated automatically using programmed algorithms (Jones et al, 2021). Study 1 also extended Zilioli et al (2014) by examining whether a suite underlying components associated RHP were also positively associated with men's fWHR: physical aggression, blunt‐force trauma resistance, and/or force output.…”
Section: The Present Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In our present study, given the large number of faces we used, we aimed to generate a subset of those physical and geometric features that could be automatically measured, but were still easily interpretable. A recent study showed that automatically measured physical and geometric features are highly correlated with those that are manually measured (Jones et al, 2021 ). Here, to automatically measure physical and geometric features, we used a pre-trained model of facial landmark detection implemented in the dlib C + + library to estimate the location of 68 key points on each face image.…”
Section: Methodsmentioning
confidence: 99%
“…Either the template can be automatically placed by software or the template can be hand-placed. Computer-generated templates are often used by computer scientists (Baddar et al, 2016;Juhong & Pintavirooj, 2017) and have been used in psychological research as well (Jones et al, 2021). Dlib is one such machine learning toolkit (King, 2009) that can be used in conjunction with other python packages to template faces.…”
Section: Figurementioning
confidence: 99%